Observation of directed low of hypernuclei 3ΛH and 4ΛH in √𝑠NN=3 GeV Au+Au collisions at RHIC - Aboona, Bassam; Deppner, Ingo Martin; Leung, Yue; Söhngen, Yannick; Weidenkaff, Philipp (Physical review letters, 2023)
We report here the first observation of directed flow ($v_1$) of the hypernuclei $^3_{Λ